EFL Students’ Perception Toward the Use of Google Translate in Translation Class - Samad, Salma; Farahdiba, Syarifah; Sunra, La (Journal of Excellence in English Language Education, 2023)
This study aims to describe the perceptions of students, find out the obstacles that students face, and explore the ways students solve the obstacles they face when using Google Translate in translation class. It uses a descriptive qualitative research method and interviews 10 students from the English Education Department class of 2019, Faculty of Languages and Literature, Universitas Negeri Makassar. The results show that Google Translate is useful in terms of being able to translate words, paragraphs, documents, pictures, and speech instantly, with the synonym feature helping students adjust the context of the translation, follow the lesson in the classroom, complete assignments, increase confidence in collecting assignments, and improve students' translation skills. However, students are aware that the translation results must be improved and that they should not rely too much on Google Translate. Furthermore, the obstacles the students face in using Google Translate are a stable internet connection, a lack of accuracy, a maximum of 5,000 words, sometimes disordered translation results, and the inability to detect images and voices properly. To overcome the obstacles, students fix the translation results by themselves, asking friends, improving pronunciation, switching to other Google Translate features, and using Grammarly or the Microsoft Word application.